The estimation of efficiency rehabilitation measures among the volley-ballers of 18–22 in the competition period of annual cycle of preparation - Ванюк [Vanyuk О.] Олександр Іванович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The estimation of efficiency rehabilitationmeasures among the volley-ballers of high qualification of 18–22 within the framework of contention period of annual cycle of preparation is conducted. It is rotined that for the sportswomen of control group, which traditional facilities of renewal were utillized, the substantial decline of their physical capacity and practically all of parameters of functional preparedness was marked completion of contention period. Opposite, plugging in the program of rehabilitation measures of volley-ballers of experimental group of antioxidant ecdisterone was instrumental in a maintainance at optimum level of their physical capacity, aerobic possibilities and functional preparedness. Results testify to high enough efficiency of the use of vegetable adaptogenes in the system of rehabilitation measures of girls-volley-ballers of this age. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>